Criminal Law Regulations Against Cyber Harassment Perpetrators Through Social Media - Ritonga, Amany Zuhairah; Marpaung, Zaid Alfauza (IHSA Institute, 2024)
This study aims to determine the criminal law regulations for perpetrators of cyber harassment through social media. Basically, problems that occur in society occur because of the reciprocal relationship that occurs due to the process of social interaction. Law Number 11 of 2008 con-cerning Information and Electronic Transactions (ITE) and Law Number 12 of 2022 concerning Criminal Acts of Sexual Violence, shows the state's commitment to providing legal protection to its citizens, especially those who are victims of sexual violence. One form of sexual crime that is given protection is electronic-based sexual violence as stated in the provisions of Article 4 letter i. The research method used in normative legal research is commonly referred to as doctrinal legal research or library research. The research approach uses qualitative analysis, legal mate-rials in the form ofprimary, secondary and tertiary legal materials. The research results con-cluded that cyberharassment through social media is a problem that affects all levels of society. Social media users who become victims of Cyberharassment often suffer from serious psy-chological impacts such as Post-Traumatic Stress Disorder (PTSD). Victims can report through the Ministry of Communication and Information or law enforcement officers. Therefore, it is necessary to regulate the law for perpetrators of cyberharassment, so that there are no more victims of such actions.